Translanguaging on Facebook: Exploring Australian aboriginal multilingual competence in technology-enhanced environments and its pedagogical implications - Oliver, Rhonda; Nguyen, B. (2017)
In this study, we explore how Aboriginal multilingual speakers use technology-enhanced environments, specifically Facebook, for their translanguaging practices. Using data collected from Facebook posts written by seven Aboriginal youth over a period of 18 months, we investigate how the participants move between Aboriginal English (AE) and Standard Australian English (SAE) creatively and strategically to express humour and group membership, and to identify as an Aboriginal person. We also observe how these practices have the potential to enhance rather than detract from their development of SAE. The findings of the study have important implications for teaching bilingual and bidialectal speakers in general and AE speakers in particular, highlighting the importance of creating a translanguaging space to enable them to maximize their knowledge and understanding of different subject matter and develop competencies in their various linguistic codes.